2020
DOI: 10.1038/s41371-020-00425-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of angiotensin receptor blocker product recalls on antihypertensive prescribing in Germany

Abstract: In Germany, ~8 million patients take angiotensin receptor blockers (ARBs) and 2.25 million of them valsartan. In 2018, contamination of generic ARBs with probable carcinogenic nitrosamines resulted in more than 30 recalls. The impact of such a huge recall has never been explored in Europe. We analyzed the utilization of valsartan, all ARBs, and other alternative antihypertensive drugs in Germany. We used our database of anonymized dispensing data from >80% of community pharmacies at the expense of the statu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
(43 reference statements)
1
16
1
Order By: Relevance
“…Similarly, an analysis conducted in Germany by Rudolph et al found an increase in alternative ARBs after the valsartan recall, but no difference in utilization of other antihypertensive classes occurred. 23 The difference in medication changes seen between the present study and other studies could be attributed to the fact that a large proportion of the patients in the present study were on valsartan 320 mg tablets. Valsartan 320 mg tablets do not have equivalent dosing when converting to losartan, which is the other preferred formulary alternative by the VA PBM.…”
Section: Discussioncontrasting
confidence: 68%
“…Similarly, an analysis conducted in Germany by Rudolph et al found an increase in alternative ARBs after the valsartan recall, but no difference in utilization of other antihypertensive classes occurred. 23 The difference in medication changes seen between the present study and other studies could be attributed to the fact that a large proportion of the patients in the present study were on valsartan 320 mg tablets. Valsartan 320 mg tablets do not have equivalent dosing when converting to losartan, which is the other preferred formulary alternative by the VA PBM.…”
Section: Discussioncontrasting
confidence: 68%
“…Drug prescriptions were analyzed using the database of the German Institute for Drug Use Evaluation (DAPI), which contains anonymous dispensing data of community pharmacies claimed to the statutory health insurance (SHI) funds and thus covers 88% of Germany's population, that is, approximately 73.3 million people. 22 All claims data from a representative sample of more than 80% (until June 2019) and more than 95% (from July 2019 onwards) of community pharmacies were available. The data were extrapolated by regional factors to 100% of the SHI‐insured population.…”
Section: Methodsmentioning
confidence: 99%
“…The database contains anonymized dispensing data on medications prescribed at the expense of the statutory health insurance (SHI) funds. The available data were extrapolated by regional factors to represent all SHI-insured persons (approximately 88% of the total German population—that is, 73.3 million people) ( 6 , 10 ). Prescriptions for privately insured patients are not covered, and no data on individual patients, treatment indication, duration, or dosages were available.…”
Section: Methodsmentioning
confidence: 99%